EMPIRICAL STUDY ON THE ROLE OF SELECTED DEMOGRAPHIC AND INDEPENDENT VARIABLES IN PROFESSIONAL CONTENTMENT OF TEACHERS - BABU, R.BABU (International Journal of Psychosocial Rehabilitation, 2020)
Teachers play a vital role in developing the knowledge and skills of youth and hence are the pillars of a Nation. Most of the institutions face challenges in attracting and retaining the quality teachers. This research work is carried out with the aim of determining the relationship of teachers professional contentment with regard to professional stress, leverage technology, teaching attitude, emotional intelligence and self-efficacy. Normative survey method is employed in this research work. In this regard stratified random sampling technique has been applied in collecting the data from the sample of 658 school teachers working in the higher secondary schools situated in the Cuddalore district of Tamil Nadu, India. Four instruments constructed and validated by the investigator namely professional contentment scale, professional stress scale, leverage technology scale, and teaching attitude scale have been used in this research. In addition, two instruments namely emotional intelligence scale and self-efficacy scale available in literature have also been used. In order to realize the objectives and testing of hypotheses descriptive analysis and differential analysis have been employed. The results of the research reveals that the dependant variable professional contentment of the entire sample show average level. All the independent variables have also show the average level as per the results from the calculations of data and interpretations. Further it is also observed that the demographic variables have shown significance as well as not significance with respect to dependent and independent variables selected for the study. The study reveals that the teachers selected for the present investigation have expressed neither high professional contentment nor low but they expressed an average. This indicates that the school teachers are neither pressurized nor pleasured with their profession but expressed moderate professional contentment.